ZnO Doping Effects on Piezoelectric and Ferroelectric Characteristics of Lead-free CuO Doped Na0.5K0.5Nb0.97Sb0.03O3 Piezoelectric Ceramics. (1st January 2015) - Chan, I-Hao; Sun, Chieh-Tze; Houng, Mau-Phon; Chu, Sheng-Yuan; Tsai, Cheng-Che; Hong, Cheng-Shong
Abstract : In this paper, the effects of ZnO doping on the piezoelectric and ferroelectric properties of lead-free Na0.5 K0.5 Nb0.97 Sb0.03 O3 -2% CuO -x% ZnO (NKNSCZ) piezoelectric ceramics were systematically investigated. NKNSCZ ceramics were synthesized using the conventional solid-state reaction method. ZnO additions had not only enhanced the piezoelectric properties kp, Qm value by interacting with CuO to form liquid phase but lowered the sintering time as well. Relatively high piezoelectric properties were obtained at x = 1.5 with kp = 0.427, kt = 0.44, ɛr = 235, Qm = 1613, tan δ = 0.45%, and density = 4.56 g/cm 3 respectively.